2017
DOI: 10.1007/s13592-017-0537-z
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of rebel workers in honeybee (Apis mellifera) colonies

Abstract: -The honeybee is one of several eusocial species in which the queen is typically the only reproductive member of the colony; worker reproduction is mostly restricted to queenless colonies. Because workers cannot mate, they lay unfertilized eggs, which develop into males. A recent study showed that in queenless colonies, which arise after swarming, worker larvae develop into rebel workers that have greater reproductive potential than do workers reared in queenright colonies, as measured by the number of ovariol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…However, the source of chemical labels has yet to be identified (Katzav-Gozansky et al 2002;Martin et al 2002;Oldroyd et al 2002). The shift in resource reallocation to reproductive tissue during development causes rebel workers, more so than normal workers, to be physiologically prepared to lay male-destined eggs and thereby produce sons of their own (Woyciechowski and Kuszewska 2012;Kuszewska et al 2017). However, the results of our experiment show that the rebel workers do not evade worker policing by laying more acceptable eggs.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, the source of chemical labels has yet to be identified (Katzav-Gozansky et al 2002;Martin et al 2002;Oldroyd et al 2002). The shift in resource reallocation to reproductive tissue during development causes rebel workers, more so than normal workers, to be physiologically prepared to lay male-destined eggs and thereby produce sons of their own (Woyciechowski and Kuszewska 2012;Kuszewska et al 2017). However, the results of our experiment show that the rebel workers do not evade worker policing by laying more acceptable eggs.…”
Section: Discussionmentioning
confidence: 72%
“…These features suggest that the rebel workers are more engaged in laying their own male-determined eggs than in rearing the queen's offspring. A recent study confirmed this suggestion, as Kuszewska et al (2017) showed that rebels lay their own eggs even in the presence of the queen. Another study showed that 15-day-old rebel workers exhibited active ovaries if they remained in a queenless or a q u e e n r i g h t c o l o n y d u r i n g a d u l t h o o d (Woyciechowski and Kuszewska 2012).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…All colonies were treated in the same way, and the experimental design was previously described by Woyciechowski and Kuszewska (2012) as well as in other papers (i.a. Kuszewska et al 2017Kuszewska et al , 2018bWoyciechowski et al 2017). At the beginning of the experiment, the queen was restricted to two experimental frames to produce eggs of a similar age (day 0).…”
Section: Methodsmentioning
confidence: 99%
“…The proximate factor that influences rebel caste development is the absence of a queen or, more precisely, the lack of a queen's mandibular gland pheromones (Woyciechowski, Kuszewska, Pitorak, & Kierat, 2017) during the larval feeding period (unsealed larvae). If they remain in a queenless or a queenright colony during their adult lifetimes, these rebel workers display active ovaries (Woyciechowski & Kuszewska, 2012) and have a higher number of male offspring than normal workers (Kuszewska, Wącławska, & Woyciechowski, 2018). The appearance of workers with mature ovaries in orphaned colonies is not surprising as workers are known to lay eggs when a colony loses its queen and there is no chance of rearing a new queen (Page & Robinson, 1994;Velthuis, 1970).…”
mentioning
confidence: 99%